Compound heterozygous Niemann-Pick Type C disease in the neonatal period - Özden Turan; Zerrin Yilmaz; Ayşe Ecevit; Deniz Anuk-ince (Journal of Contemporary Medicine, 2021)
Yenidoğan döneminde birleşik heterozigot Niemann-Pick Type C hastalığı